ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI KOPI MULO DI KOTA TIMIKA - Renzo Kalvien Palino Ada’; Siske Tontong (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the effect of the marketing mix on consumer satisfaction at mulo coffee shops, the influence of the marketing mix on purchasing decisions at mulo coffee shops and the effect of the marketing mix on purchasing decisions at mulo coffee shops through consumer satisfaction. The population in this study were mulo coffee shop consumers with a sample of 100 respondents. Sampling using random sampling technique. Data collection techniques through questionnaires and documentation. The data analysis technique used in this study is the Path analysis technique. The results showed that the marketing mix (product, promotion, price and place) had a significant effect on consumer satisfaction at the mulo coffee shop, namely the price variable with a value of tcount (3.033) ≥ ttable (1.985). The marketing mix (product, promotion, price and place) that has a significant effect on purchasing decisions at the Mulo coffee shop is the price variable with a tcount of (3.093) ≥ ttable (1.986). None of the four marketing mixes has a significant influence on purchasing decisions through customer satisfaction at the mulo coffee shop